Ranking Social Problems from Students' Perspectives in Tabriz University of Medical Sciences - Delara Laghousi; Mahasti Alizadeh-Mizani; Narges Bashirivand; Rahimeh Laghousi; Bahar Zamiran (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: In order to plan scientific and socially- realistic program and with regard to the limited facilities and capacities of society, it is necessary to prioritize social problems and gradually plan to control them. The aim of this study was to evaluate students' perspectives of Tabriz University of Medical Sciences on social problems in campus and community. Materials and Methods: This study was a cross-sectional research carried out in Tabriz University of Medical Science in summer of 2017. After designing the questionnaire and evaluating its validity and reliability, the self-administered questionnaire was completed by 370 students. Convenience sampling method was used. Friedman test was applied to rank social harms. After data collection, data was entered into SPSS software version 16, and ranked social harms based on the mean rank scores of each item. Results: From the students' point of view, unemployment with a score of 19.3, poverty 17.3, addiction 16.6, nepotism 16.6, and high prices 15.4 were the major social harms in the community. Nepotism 9.2, lack of motivation 8.6, lack of job conscience 8.4, discrimination 7.8 and brain drain 7.3 were the major social harms in the campus. There was a significant difference between the views of female and male students on social harm in the campus regarding alcohol consumption, nepotism and dropout. However, there was no statistically significant difference between the views of native and non-native students on social harms in campus. Conclusion: The findings of this study indicated that from the students' point of view, unemployment, poverty, ‎and addictions are the major social harms in the community. In addition, nepotism, lack of ‎motivation, lack motivation, and lack of job conscience are ‎the major social harms in campus. DOI: http://doi.org/10.22037/ch.v6i3.22509